The prevalence of cardiovascular disease risks among working people Malaysia: findings from the National Health and Morbidity Survey 2015 / S Maria Awaluddin ... [et al.] - Awaluddin, S Maria; Kuay, Lim Kuang; Shawaluddin, Noor Syaqilah; Tuan Lah, Tuan Mohd Amin; Muhamad Robat, Rosnawati; Mahjom, Maznieda; Mohd Yussof, Muhammad Fadhli (Faculty of Medicine, 2023)
Introduction: Cardiovascular disease (CVD) is prevalent globally and associated with the risk of premature mortality among the economically productive population. This article aimed to determine the prevalence of seven types of diseases and risk factors that contribute to CVD among working people (18-64 years) in Malaysia. Methods: A cross-sectional study among a nationally representative sample in Malaysia was conducted using a validated questionnaire. Registered nurses performed the clinical procedures to measure glucose, cholesterol, body mass index and blood pressure. The prevalence was calculated via the complex samples menu of the IBM SPSS version 25 data analysis to ensure population representativeness. Results: The overall prevalence of CVD risks among working people was 14.1%, 17.3%, 24.5%, 28.3%, 31.7%, 45.9% and 94.2% for diabetes, obesity, hypertension, inactive, tobacco smoking, hypercholesterolemia and inadequate fruit and vegetable (FV) intake, respectively. This study found that the older age group of working people has a higher prevalence of diabetes, hypertension, and hypercholesterolemia. In terms of gender, males significantly have a higher prevalence of hypertension and tobacco smoking than females. Whereas females significantly have a higher prevalence of hypercholesterolemia, obesity, and physically inactive than males. Those who worked as a manager & senior officials and clerical workers were inactive, while skilled workers had the highest prevalence of tobacco smoking at 60%. Conclusions: This study highlighted that working people have significant CVD risks and they vary according to socio-demographic and occupational characteristics. Thus, a workplace intervention should be conducted by the employers in line with the mainstream health services at the health facility to reduce premature morbidity and maintain productivity.